Progressivism and Reconstructionism in the Philosophy of Education: A Critical Review from the Perspective of Islamic Education - Mashfiyatus Shidqiyyah; Muhammad Arif Syihabuddin (Aslim: Journal of Education and Islamic Studies, 2026)
Progressivism and reconstructionism are two modern schools of educational philosophy that developed in response to social change and dynamic educational needs. Progressivism emphasizes education as a process oriented toward learning experiences and the active development of student potential, while reconstructionism views education as a strategic means for social change and reconstruction. This study aims to analyze the nature and principles of progressivism and reconstructionism, and to examine their relevance and position within the perspective of Islamic education. This study employed a qualitative approach with library research, with data sources consisting of modern educational philosophy literature and classical Islamic education texts. Data analysis was conducted descriptively and analytically with a comparative approach. The results indicate that both schools of thought have common ground with Islamic education, particularly in the development of students' intellectual potential, personality formation, and social responsibility. However, Islamic education has a normative foundation derived from the Qur'an and Sunnah, so acceptance of progressivism and reconstructionism is selective and critical. Therefore, both schools of thought can serve as material for dialogue and enrichment of thought in the development of Islamic education as long as they remain within the framework of Islamic values.